A Dual Threat: Redox‐Activity and Electronic Structures of Well‐Defined Donor–Acceptor Fulleretic Covalent‐Organic Materials. Issue 15 (12th February 2020) - Leith, Gabrielle A.; Rice, Allison M.; Yarbrough, Brandon J.; Berseneva, Anna A.; Ly, Richard T.; Buck, Charles N.; Chusov, Denis; Brandt, Amy J.; Chen, Donna A.; Lamm, Benjamin W.; Stefik, Morgan; Stephenson, Kenneth S.; et al.
Abstract: The effect of donor (D)–acceptor (A) alignment on the materials electronic structure was probed for the first time using novel purely organic porous crystalline materials with covalently bound two‐ and three‐dimensional acceptors. The first studies towards estimation of charge transfer rates as a function of acceptor stacking are in line with the experimentally observed drastic, eight‐fold conductivity enhancement. The first evaluation of redox behavior of buckyball‐ or tetracyanoquinodimethane‐integrated crystalline was conducted. In parallel with tailoring the D‐A alignment responsible for "static" changes in materials properties, an external stimulus was applied for "dynamic" control of the electronic profiles. Overall, the presented D–A strategic design, with stimuli‐controlled electronic behavior, redox activity, and modularity could be used as a blueprint for the development of electroactive and conductive multidimensional and multifunctional crystalline porous materials. Abstract : A journey into the deep confines of the forest can sometimes lead to new discoveries. Electron acceptors prepared themselves for travel into the unknown of the COF electron‐donating "forest". Instead of getting lost in the deep, dark forest, the acceptor‐based (purely organic) covalently bound, crystalline, and porous scaffolds exhibited not only increases in conductivity, but also retention of the redox‐active nature.